A Study Of The Teaching English For Young Learners At Islamic Elementary School Islamiyah Malang - Muhammad A. Zamzami (Akademika: Jurnal Manajemen Pendidikan Islam, 2019)
In Indonesia, English is a foreign language which is considered important to absorb and develop science and knowledge, technology, art, and to improve the relationship among the countries in the world. Consequently, English is important to be studied. It is better to be taught in the earlier time. The objective of English program of elementary school is to enable the students to comprehend simple oral and written expression, and to prepare the students for further education in the secondary school. This research used descriptive qualitative and quantitative design, which tries to get the description of the teaching and learning at MI Islamiyah Malang, The subjects of this study are the English teacher, and the students of fifth grade A. There are two classes in fifth grade: fifth-grade A and fifth-grade B. But the researcher took fifth-grade A as the subject. The data of this study are from the observation in the classroom, interview, questionnaire, and documentation. The observation is done to collect the data about the activities of the students and the teacher in the classroom. Interview is used to answer the research problems dealing with: 1) the curriculum of MI Islamiyah Malang, 2) the teacher's qualification, 3) the use of media, 4) techniques of teaching English, 5) the evaluation of teaching, and 6) English achievement. Then interview is used to support the data about techniques of teaching English and the use of media. The last data is documentation is used to support the data gathered through observation by taking pictures of teaching and learning activities in the classroom.